Ftom the history of establishmentnational organizations in Uzbekistan - Ubaydullaev, Uktamjon (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
In this article is investigated establishment and functioning of the organizations “national charge” and “national independence” against the soviet system by the helping archive sources and historical literatures as well